Estudio farmacocinético comparativo entre diazepam y midazolam, post administración intravenosa e intramuscular en avestruz doméstico (Struthio camelus) - Olivos O., Luis (2001)
Our interest in handling animal species with the purpose of experimentation and pharmacokinetic study, due to the necessity of more rational guidelines, have motivated us to develop the present study in six healthy young ostriches to whom we administered diazepam (DZP) and midazolam (MDZ) via IV and IM in a simple dose of O,5mg/kg. By HPLC/u.v quantification (220nm) we observed that pharmacokinetics parameters of DZP after IV administration, corresponded to MRTt=71,17±29,97min, t1/2β=49,30±21,18min, Cl=87±50mLlkglmin and Vcc=1,82±O,35L/kg. The plasma DZP concentrations post IM administration and the two main active metabolites concentrations after IV/IM administration did not allow a kinetic treatment of them. The pharmacokinetics parameters of MDZ after IV and IM administration respectively corresponded to MRTi=59,70±37,14 and 50,09±12,71min, t1/2β=39,64±25,30 and 35,32±1O,93min, Cli=37±20L/kg/min and Vc=O,72±O,24L/kg. The bioavailability after IM administration was 99,97±30,43% with Cmax=O,36±O,09¡,μ,g/mL and tmax=11±2,24min. The plasma concentrations of l-hidroxi-midazolam (active metabolite) were not detected. A correlation between the laboratory data and the clinical observations in situ have been stablished. We conclude that DZP was not a valid option for treatment of anxiety or anesthetic induction in young ostriches. On the other hand, MDZ demonstrated a significant depression of the CNS, by both ways. The technique used was reliable according to the validation parameters employed.